Motivos e consequências da falência de agroindústrias canavieiras no estado do Paraná - Clein, Claudelir (2021)
Brazil is one of the largest producers of cane, sugar, and ethanol in the world, generating a foreign exchange of approximately US$ 5.5 billion with sugar exports and US$ 981.9 million with alcohol exports, in addition to maintaining thousands of jobs. Nevertheless, the sugarcane agribusinesses is experiencing a crisis in the sector, causing severe losses, problems of judicial recovery, and several plants' bankruptcy. Given this, the present study sought to highlight and analyze the reasons and consequences of the sugarcane agribusinesses bankruptcy in the State of Paraná. For this purpose, two methodological approaches concatenated with each other were used, a quantitative one and a qualitative one. The dynamic panel data model sought to verify how the GDP of five cities in Paraná (Cambará – operated the Casquel plant; Engenheiro Beltrão – Sabarálcool/Headquarters; Perobal – Sabarálcool/Branch; Porecatu – Central do Paraná; and Rolândia – Corol), where sugarcane agribusinesses existed as driving forces and went bankrupt. The independent explanatory variables for GDP behavior were the outdated GDP for one period; IFDM – Firjan Municipal Development Index – education; IFDM employment; harvested area; Locational Quotient (QL), both positively related to the dependent variable (GDP). The other variables showed a negative relationship (agricultural jobs; experience factor – average years of experience of the municipality’s workers; male labor), implying an elasticity in which the increase in one of these variables decreased the GDP. The quantitative analysis contributions suggest that the GDP of the five municipalities studied was related to the collapse of the plants in a way. According to ten representatives of the public and private sectors (in general), the qualitative method's results (field research in the municipalities mentioned above) showed reduced jobs, income, and collection. As for the factors considered decisive for the closure of the surveyed units, it was found that the lack of management was the main reason for plant failure, according to the perception of the ten interviewees. Comparing the two approaches, quantitative and qualitative, the logic of some variables that resulted in explanations corroborates the GDP performance in the five municipalities visited, for example, when several respondents pointed out that the plants' collapse made room for other activities, this is related to the QL in the econometric analysis. In other words, when the plants went bankrupt, agriculture started to be less concentrated (relatively), failing to focus on a specific activity.